From leaf to cup: critical points of halal compliance in artisan tea - Rusdah , Rusdah; Budiyoko, Budiyoko (Journal of Halal Product and Research (JHPR), 2025)
Indonesian tea consumption has posted a consistent upward trend, both in volume and market demand for a greater variety of tea products. Among the popular new varieties is artisan tea, which is a creatively crafted blend of tea leaves mixed with natural ingredients such as spices, flowers, and dried fruits to produce distinctive tastes and a good appearance. Although the ingredients used are plant-based and generally halal, the artisan tea manufacturing process can still include critical control points that require rigorous halal testing. The goal of this study is to identify and assess the halal critical points of artisan tea manufacturing according to three aspects: raw materials, manufacturing process, and packaging materials. A qualitative descriptive research design was utilized, including literature review, direct observation of the manufacturing process, and analysis using the halal critical point decision tree framework. It discovers that possible points of halal criticality at the artisan stage of tea-making pertain almost solely to packing material—essentially those bearing plastic-based or synthetically embedded material, those occasions of mixing handled manually as perhaps a hazard against contamination, and storage needs such that protective containment from access of uncleaned substances or cross-contamination should be required. In contrast, ingredients such as green tea, dried mint leaves, and Indian cardamom, being the major ingredients, when used in their dry forms, are usually exempted from having severe halal concerns on account of their plant origin and minimal processing and are thus inherently halal.   Keywords: Tea, Artisan Tea, Halal Critical Points, Halal